Identification of SSR Markers for Differentiating Rice (Oryza sativa L.) Varieties Marketed in Turkey - NECMI Beser; ZEYNEP ÇİSEM Mutafçılar (Journal of Agricultural Sciences)
This study was carried out to identify SSR markers for the differentiation and identification of rice cultivars marketed in Turkey between 2016 and 2017. In this study 60 registered orproduction permitted, some local and foreign rice varieties were used as a material. DNA was isolated from single polished rice kernels for PCR amplification and rice cultivars were genotyped by 50 SSR markers. We found that 45 out of 50 SSR markers produced reproducible and polymorphic alleles. Thirty-six rice varieties had variety specific alleles among 60 rice varieties analysed in the study. This variety specific alleles belong to only one variety and they can be used to identify rice variety among 60 rice varieties studied. Osmancık-97, Cammeo, Ronaldo and Baldo are the most import 4 varieties in Turkish rice production and milled rice market. In this study, it was found that RM152, RM144, RM259 and RM118 SSR markers can be used to differentiate and identify these most important four varieties with different combinations. Collectively, this study provided some variety specific SSR markers that can be used to differentiate and identify rice varieties sold in Turkey.